Genetic and Clinical Evaluation of Retinitis Pigmentosa - Leyla Eryiğit Eroğul; Ayça Nur Demir; Hamidu Hamisi Gobeka; Mustafa Doğan; Muhsin Elmas; Özgür Eroğul (Journal of Contemporary Medicine, 2022)
Background: The aim of this study was to evaluate the most common underlying genetic and clinical etiologies of retinitis pigmentosa (RP) disease in our geographical area. Material and Method: In our archive, there are about 3000 patients who applied to our clinic between the years 2015-2021. The files of approximately 700 patients with a definitive genetic diagnosis were retrospectively scanned. A definitive genetic diagnosis was made in 22 of these patients. During our research, we collected some clinical parameters including the prenatal, natal, and postnatal history of the patients, history of surgery and seizures, and family history. In family history, we did a detailed pedigree with at least 3 generational analyses, questioned parental kinship, looked for similar members in families, and identified inheritance patterns of their disorder. We draw 3 generations pedigree and we collected peripheral venous blood samples from patients and sent them to a commercial lab for gene panels or WES. After obtaining the definitive genetic diagnosis of all patients, we compiled a table with the other parameters we questioned. Results: As a result of our WES analysis in patients 1 and 2, homozygous c.1331_1332 dupAG/p. Thr445ArgfsTer10 Class 2 variant was detected in the POC1B gene of patient #2.In the RP panel 1 reports of patients 3 and 4, the genomic alteration of c.2254dupA (p.Ser752Lysfs*14) was detected in exon 15 of the ABCA4 (NM_000350) gene. Patient 5, EYS c.4964T>C heterozygous. Patient 6. SEMA4A C.1168A>G (heterozygous). Patient 7, SEMA4A C.1168A>G (heterozygous), RP1 c.5402C>T (heterozygous), CGNB1 c.1382C>T (heterozygous).Patient #8, . Heterozygous variation of p.Thr390Ala (c.1168A>G) in the SEMA4A gene is present.As a result of our WES analysis, a homozygous c.2021C>A/p.Pro674His Class 2 variant was detected in the RPGRIP1 gene of patient #9. Heterozygous c.119-2A>C Class 1 mutation was detected in the NR2E3 gene of patient 10. Homozygous c.271C>T/p.Gln91* Class 1 mutation was detected in the MFRP gene in patient 11. Patient #12 was diagnosed at the age of 7-8 years. When we look at the exome sequencing results, a homozygous mutation in the CNGB1 gene c.413-1G> of patient 13 was detected. Heterozygous p.Ser361Tyr (c.1082C>A) change detected in the ABCA4 gene of patient #14 was detected. The heterozygous p.Glu150Lys (c.448G>A) change detected in the RHO gene of patient #15 was pathogenic according to ClinVar database and in silico analysis. rated as. Prediagnosis was Bardet-Biedle Syndrome in patient 16. P.Gly244Asp change was detected in RPE65 gene of patients 17 and 18. Automated DNA sequencing of patient #19 and patient #20 results in a homozygous sequence variation in the coding sequence of the NR2E3 genes, a homozygous CGG>CAG nucleotide substitution, and an amino acid replacement of Arg311Gln. Heterozygous mutation was detected in the same gene region in patient 21 (fathers). Variation in NR2E3 is the most likely cause of these patients' eye condition, as it is a complete genotype and is strongly associated with RP in many published families. Genetic results on an allele of the BBS1 gene of patient 22 (chr11:66.278.121-66.291.364 (13.2kb)/ISCN: seq [GRCH37]11q13.2(66.278).121-66.291.364)x1). The other allele has a heterozygous point mutation (c.1424dupT p.Ser476fs-rs886039798). Conclusıons: As determined in our study, the disease can be encountered with many different genetic etiologies. In this regard, patients undergoing genetic testing should be carefully examined for both SNP (single nucleotide polymorphism) and CNV (copy number variation).In addition, before genetic tests are performed, it should be well determined whether there is an isolated RP or an accompanying RP. In this respect, patients should be evaluated by making a detailed anamnesis and physical examination and drawing a pedigree containing at least 3 generations. Therefore, it was concluded that accompanying abnormalities should also be examined in the evaluation of retinitis pigmentosa anomalies.